Philosophy of Islamic shari'ah and its contribution to the science of contemporary law - Kharufah, Ala al-Din (Islamic Research and Training Institute, 2000)
Islamic law; philosophy; law; 20th century
Original title; Falsafat al-tashri al-Islami wa-mada musahamatiha tujaha ilm al-qanun al-muasir
Keywords: Islamic law -- Philosophy; Islamic law -- 20th century.; Law -- Islamic countries